Bevacizumab for CRVO Associated CME: Effect of Timing and Frequency of Injections on Final Visual Outcome - Joseph Pikkel; Otzem Chassid; Yumna Busool; Ward Srour; Adi Sharabi-Nov; Itzchak Beiran (Journal of Ophthalmology)
Purpose. Injection of anti-VEGF antibody into the vitreous body is a well-established treatment for ischemic central retinal vein occlusion (CRVO) associated macular edema. Various treatment regimens regarding the timing, number, and frequency of injections have been proposed. Methods. We reviewed the medical records of 68 patients treated by intravitreal bevacizumab (Avastin) injections for macular edema due to CRVO. We examined final visual acuity six months following the last injection in relation to injection policy (one primary injection followed by subsequent injections based on anatomical response versus a prescheduled protocol of one injection per month for the first 3 months) and in relation to the time lapsing from CRVO diagnosis to the first injection. Results. Mean visual acuity improved more for patients treated by a protocol of 3 prescheduled injections than for those treated with one primary injection. Improvement in mean visual acuity was greater for patients who received their first injection within the first month than those treated after 3 months (P<0.01). Conclusion. A protocol of three prescheduled injections of bevacizumab, starting within one month of a CRVO event, was associated with better visual outcome compared to single injection and/or treatment starting more than 3 months following the time of diagnosis.